Traditional Eco-Friendly Practices and Modern Green Marketing Adoption in Manipur: A Management Perspective - Makakmayum, Baadshah; Md. Mustafin Ahmed (Universitas Airlangga, 2026)
This new concept of the business in the 21st century is depicted as a green marketing since it adds the environmental concern to its rivals in the market. Such a phenomenon, in the case of India North-eastern state of Manipur, has acquired the specifics, since in this region the entire history of environmentally friendly activity is played out in the cult. The paper examines the relationship between consumer awareness, demographic parameters and indigenous ways and their effects on adoption of green marketing in the state of Manipur. The authors employ a survey of 200 respondents to test different four hypotheses with the help of descriptive statistics, correlation, and chi-square and investigate awareness, traditional practice, demographics, and eco- label trust. It is identified that the awareness and cultural continuity have significant role to play on adoption whereas education and income have significant role to play on green consumption instead of age or gender. Also, the readiness of consumers to pay extra price on eco-labelled products rises due to such confidence. The evidence underpins the management relevance of the coherence between cultural identity and the modern sustainability practices and highlights the immense possibility that Manipur has in green marketing management.